Tire-breeding mosquitoes of public health importance along an urbanisation gradient in Buenos Aires, Argentina - Rubio, A. (2011)
Used vehicle tires are a source of mosquito vectors and a means of their introduction and expansion. With the aim of assessing the effects of urbanisation on the main mosquito vectors in temperate Argentina, the infestation levels of Aedes aegypti (L.) and Culex pipiens L. were studied in used tires from highly urbanised cities to low-urbanised small towns in Buenos Aires. Immatures of both species accounted for 96% of the 9,722 individuals collected; the total individuals collected represented seven species. The percentage of water-filled tires containing mosquitoes [container index (CI)] was 33% and the percentage of infested sites [site index (SI)] was 65.2%. These indexes decreased significantly from low to high urbanisation levels for both mosquito species. The relative abundance (RA) of Ae. aegypti immatures was slightly higher toward large cities, but showed no difference for Cx. pipiens. The CI of shaded tires was significantly higher than the CI of exposed tires for both mosquito species. There was no difference in RA values between shaded and sunlit tires. The CI and the SI were highest during the summer across the urbanisation levels, except for Cx. pipiens, which continued to increase during the autumn in small towns. Results related to urbanisation gradient, sunlit exposure and seasonality are discussed.